Climate Change Theater and the Interrelation of Human and the More-Than-Human - Färber, Andrea (AmLit)
Being one of the most pressing issues of our times, climate change threatens the safety of the planet. As of now, however, only a fraction of people is seriously affected by the looming crisis. This paper concerns itself with how climate change theater can help raise awareness of the already existing impacts, both for humans and the more-than-human. Considering the issue of culture/nature dualism and the necessity to recognize the more-than-human as equal in order to bring along change, it is argued that sympathy needs to be elicited from the audience to influence their opinion of the importance to combat climate change. Subsequently, the influence of arts on the general public on the basis of case studies as well as the concept of affective ecology are introduced to showcase how climate change theater can actually make a difference by influencing audiences through embodied simulation. An analysis of the play Sila by Chantal Bilodeau highlights in which ways both foreign cultures and places as well as different species can be utilized to evoke sympathy in the observer. The importance of relationships, shared spaces and shared emotions, as well as the traditional Inuit concept of sila – a component of everything in existence – emphasize the importance of interconnectedness in climate change theater. The play utilizes both humans and the more-than-human to portray the lived experience of climate change in the Arctic to an audience not yet affected by it.